«The absurdity of being trapped in blood-beating matter»: On drugs and literature in Ingvar Ambjørnsen’s ’Skogens hjerte’ - Jager, Benedikt (Nordlit, 2022)
This article explores Norwegian author Ingvar Ambjørnsen’s short story «The Heart of the Forest» from his collection Dark Dawn (1997) and focuses on the story’s prime experience, that of drugs. Peter Sloterdijk’s account of the historical development of drugs from the early Greek era to modernity is the theoretical framework. His understanding is found in Ambjørnsen’s short text, which also contains a notion of intertextuality. Therefore, the article highlights both literary (Vesaas) and philosophical references (Huxley). «The Heart of the Forest» is also the precursor for Ambjørnsen’s novel The Night Dreaming of Day (2012), which implies that the author sampled his own short story and gave it a pessimistic reinterpretation.